2021
DOI: 10.3390/ijerph182212105
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Diseases: A Comprehensive Review on Risk Factors, Immunological Mechanisms, Link with COVID-19, Potential Treatments, and Role of Allergen Bioinformatics

Abstract: The prevalence of allergic diseases is regarded as one of the key challenges in health worldwide. Although the precise mechanisms underlying this rapid increase in prevalence are unknown, emerging evidence suggests that genetic and environmental factors play a significant role. The immune system, microbiota, viruses, and bacteria have all been linked to the onset of allergy disorders in recent years. Avoiding allergen exposure is the best treatment option; however, steroids, antihistamines, and other symptom-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 238 publications
(227 reference statements)
3
23
0
Order By: Relevance
“…As predicted by the hypothesis of this study, here we have demonstrated that BNT162b2 may elicit bronchospasm in hyperreactive airways, and that this detrimental effect results after a single administration, thus with no involvement of allergic sensitization mechanisms due to repeated exposures [ 67 ]. Certainly, we have ruled out that the increased AHR could be related to the active component tozinameran; conversely, we have proven that it is associated with some excipient, perhaps ALC-0159.…”
Section: Discussionmentioning
confidence: 56%
“…As predicted by the hypothesis of this study, here we have demonstrated that BNT162b2 may elicit bronchospasm in hyperreactive airways, and that this detrimental effect results after a single administration, thus with no involvement of allergic sensitization mechanisms due to repeated exposures [ 67 ]. Certainly, we have ruled out that the increased AHR could be related to the active component tozinameran; conversely, we have proven that it is associated with some excipient, perhaps ALC-0159.…”
Section: Discussionmentioning
confidence: 56%
“…First, this decrease could be attributed to the relationship between infectious and allergic diseases. Infectious agents have been identified as the causative factors of allergic diseases [ 8 ]. Respiratory infections caused by viruses, such as rhinoviruses and respiratory syncytial virus, have been recognized as the dominant causes of symptom exacerbation in patients with asthma [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, allergy and asthma development are distinct though they are both inflammatory diseases and share some common risk factors. Some of the common risk factors between allergic sensitization and asthma development include race, sex, heredity, pollution, passive smoking, obesity, and respiratory viral infection (94,95). Dzidic et al found associations between oral bacteria composition and allergy and asthma development during a 7-year longitudinal study in which DNA from salivary samples was isolated from children at 3, 6, 12, 24 months, and 7 years of age who were developing allergic symptoms and sensitizations (n = 47) and from children with no clear allergic symptoms (healthy) up to 7 years of age (n = 33) (Figure 3) (32).…”
Section: Oral Microbiota Composition May Influence Allergies and Resp...mentioning
confidence: 99%